FIDIC 2017 : a definitive guide to claims and disputes - Brown, Nicholas A. (ICE Publishing, 2021)
This is an essential reference on the claim and dispute resolution procedures in the second edition of the FIDIC contract suite. The book provides an accessible introduction with a user-friendly layout, and will also be an authoritative source of information on the new procedures for claims and disputes that were introduced in the FIDIC 2017 suite of contracts.